ANALISIS STRATEGI AKTOR DALAM PEMEKARAN CIANJUR SELATAN SEBAGAI DAERAH OTONOM BARU - sandi maftuh firdaus; Denny Hernawan; G. Goris Seran (Jurnal Governansi, 2018)
The purpose of this study are (1) identifying the network of South Cianjur Expansion policies, (2) knowing the obstacles that exist in the South Cianjur Expansion process, (3) knowing the Actor Strategy in South Cianjur Expansion. This research uses policy analysis theory in this case the Policy Network involved in the process of determining the policy of the expansion of South Cianjur as a New Autonomous Region. This study uses qualitative methods, namely research that produces descriptive data in the form of written or oral words from people and observable behavior. The results of this study indicate that the actors involved in the expansion process of South Cianjur show the problems that arise in the process of the expansion of South Cianjur both internal and external problems. Internal commitment is in the form of the lack of a common understanding in looking at the expansion of South Cianjur, while the external problems are more to regulations in the form of Government Regulations related to Regional Arrangements that are still under discussion in the central government. Therefore, there needs to be good communication between the expansion and the regional government in order to produce a common thought in the expansion of South Cianjur as a New Autonomous Region.Keywords: Strategy of Actors, New Autonomous Region, South Cianjur.